2017
DOI: 10.1080/14756366.2017.1363743
|View full text |Cite
|
Sign up to set email alerts
|

New quinoxalinone inhibitors targeting secreted phospholipase A2 and α-glucosidase

Abstract: Elevated blood glucose and increased activities of secreted phospholipase A2 (sPLA2) are strongly linked to coronary heart disease. In this report, our goal was to develop small heterocyclic compound that inhibit sPLA2. The title compounds were also tested against α-glucosidase and α-amylase. This array of enzymes was selected due to their implication in blood glucose regulation and diabetic cardiovascular complications. Therefore, two distinct series of quinoxalinone derivatives were synthesised; 3-[N′-(subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…IC 50 values for compounds 9 – 11 were less than IC 50 values of standard antidiabetic drug (acarbose). These results are in concordance with some previous studies with quinoxalinones, that indicated that this type of scaffolds can inhibit α‐glucosidase and have antidiabetic properties . The results suggest that compounds 10 and 11 could be further analyzed as new potential control postprandial hyperglycemia compounds.…”
Section: Resultssupporting
confidence: 92%
“…IC 50 values for compounds 9 – 11 were less than IC 50 values of standard antidiabetic drug (acarbose). These results are in concordance with some previous studies with quinoxalinones, that indicated that this type of scaffolds can inhibit α‐glucosidase and have antidiabetic properties . The results suggest that compounds 10 and 11 could be further analyzed as new potential control postprandial hyperglycemia compounds.…”
Section: Resultssupporting
confidence: 92%
“…Quinoxalinone derivatives with dual activities on biochemically unrelated enzymes, but mutually involved in diabetes and its complications, were presented [96]. All of the studied compounds showed low micromolar IC 50 values against the different sPLA 2 isozymes (IC 50 s < 20 μM) and satisfactory IC 50 values (IC 50 s < 50 μM) against pancreatic α-glucosidase.…”
Section: Inhibitors Of Secreted Phospholipase Amentioning
confidence: 99%
“…Alasmary et al reported details of the interaction between the flavonoid quercetin and an active site of α-glucosidase, including a stacking interaction in the aromatic rings (A and B rings) of quercetin and the amino acid residue Trp432 in α-glucosidase, hydrogen bonds between the hydroxyl group in quercetin and residues Asp568, His626, and Asp357 in α-glucosidase, and hydrophobic interactions between the hydroxyl group in quercetin and residues Phe601 and Trp329 in α-glucosidase. 27 As quercetin exhibits a planar structure resulting from the conjugated system with an α,β-unsaturated ketone, it can bind to the active site of α-glucosidase. As SibC exhibits a highly planar structure and a molecular size similar to that of quercetin, we predicted that SibC could fit easily into the active site of α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%